Investigation of flow and heat transfer performance of the manifold microchannel with different manifold arrangements. (June 2022) - Chen, Chaowei; Wang, Xinyu; Yuan, Baoqiang; Du, Wenjing; Xin, Gongming
Abstract: The manifold microchannels (MMC) plays an essential role as an efficient method for heat dissipation in electronic devices. In this study, the flow and heat transfer characteristics of MMC with different manifold structures are investigated by numerical simulation. The results show the excellent effect of manifold optimization in alleviating the uneven fluid distribution between the microchannels and reducing the pressure loss of the MMC. It is observed that manifold optimization reduces the thermal resistance and temperature difference of the MMC. Finally, the comprehensive performance of different manifold structures is evaluated by the PEC value and their relationship among the pressure drop ratio, temperature difference ratio and thermal resistance ratio. And it is found that the parabolic-type manifold provides the best comprehensive performance. By analyzing the effect of conical manifold, parabolic manifold and elliptical manifold on the flow distribution, it was concluded that the uniform distribution of fluid in the MMC can be achieved by controlling the converging rate of the manifold. Highlights: The pressure drop of the manifold microchannel with tapered-type manifold is the smallest. The optimized structures of manifold can improve uneven flow distribution among microchannels. Parabolic-type manifold demonstrates the best comprehensive performance. Uniform distribution of fluid can be achieved by controlling the arrangement of the manifold.